The p53 mRNA: an integral part of the cellular stress response - Haronikova, Lucia; Olivares-Illana, Vanesa; Wang, Lixiao; Karakostis, Konstantinos; Chen, Sa; Fåhraeus, Robin (Nucleic acids research, 2019)
A large number of signalling pathways converge on p53 to induce different cellular stress responses that aim to promote cell cycle arrest and repair or, if the damage is too severe, to induce irreversible senescence or apoptosis. The differentiation of p53 activity towards specific cellular outcomes is tightly regulated via a hierarchical order of post-translational modifications and regulated protein-protein interactions. The mechanisms governing these processes provide a model for how cells optimize the genetic information for maximal diversity. The p53 mRNA also plays a role in this process and this review aims to illustrate how protein and RNA interactions throughout the p53 mRNA in response to different signalling pathways control RNA stability, translation efficiency or alternative initiation of translation. We also describe how a p53 mRNA platform shows riboswitch-like features and controls the rate of p53 synthesis, protein stability and modifications of the nascent p53 protein. A single cancer-derived synonymous mutation disrupts the folding of this platform and prevents p53 activation following DNA damage. The role of the p53 mRNA as a target for signalling pathways illustrates how mRNA sequences have co-evolved with the function of the encoded protein and sheds new light on the information hidden within mRNAs.
Keywords: Animals; Stress, Physiological; Tumor Suppressor Protein p53; 5' nepřekládaná oblast; protoonkogenní proteiny c-mdm2; vazba proteinů; lidé; 3' nepřekládaná oblast; messenger RNA; 3' Untranslated Regions; fyziologický stres; Ligands; RNA, Messenger; Proto-Oncogene Proteins c-mdm2; riboswitch; 5' Untranslated Regions; Riboswitch; nádorový supresorový protein p53; zvířata; Protein Binding; ligandy; Humans